The Factors Affecting the Students’ Low Accumulative Averages at Palestine Technical university- Khadoorie from The Students’ Point of View - Abu Sa'a, Jaafar Wasfi (Journal of Educational and Psychological Sciences, 2019)
This study aimed to investigate the factors affecting the students’ low accumulative averages at Palestine Technical university- Khadoorie from the students’ point of view using the descriptive analytical approach. The research tool was a four-dimensional questionnaire reflecting the potential factors affecting the students’ low accumulative averages, namely: personal factors, socio-economic, factors, educational factors, and environmental and physical factors. For the purpose of this study, these factors were tested on a random sample of (354) male and female students from different faculties at the university. The study showed the following results: - The overall average of the factors affecting the students’ low accumulative averages at Palestine Technical university- Kadoorie from the student’s point of view was (3.08); that is, "medium" in words. Concerning the four dimensions, the overall average of the educational factors was (4.06), followed by socio-economic factors with an overall average of (4.05), then personal factors with an overall average of (4.03). All of the three aforementioned dimensions had a “high” rating, while the environmental and physical factors lastly had a “medium” rating with an overall average of (3.16). - With reference to the variables of gender, faculty and academic level, no statistical differenceswere found between the factors affecting the students’ low accumulative averages at Palestine Technical university- Khadoorie from the student’s point of view. In light of the findings, a number of recommendations and suggestions to improve the students’ low accumulative averages and reduce the factors leading to low accumulative averages have been made for the university. First of all, a course that introduces students to university life, its requirements, and the laws and regulations in force at the university should be offered. Secondly, workshop son questions preparation and formulation should be held for the university faculty members. Moreover, poor students should be helped in order to be fully committed to education.